Multi-center living liver donor quality of life survey up to 20 years after donor hepatectomy and association with surgical outcomes. Issue 11 (November 2022) - Andacoglu, Oya; Sabisch, Eva; Malamutmann, Eugen; Ozbek, Umut; Emre, Anilalp; Tokat, Yaman; Oezcelik, Arzu
Abstract: Background: We implemented a multicenter interview with the donors to investigate Quality of Life (QoL) up to 20 years following donation. Methods: Data were collected retrospectively. Complications were graded by Dindo–Clavien classification. Results: Median follow-up was 16.1 years. Out of 485 donors, 272 responded (56.1%). The majority (>90%) reported they are in excellent/good overall health and positive or no impact of donation on professional life. Length of stay (LOS) was associated with impact on professional life and return to baseline functionality (both p = 0.046). Major complication was not associated with current physical condition or return to baseline normalcy (p = 0.06). Seventy-five (27.5%) reported unsure or no to donate again. None of the parameters were associated with donation again response. Faster return to baseline functionality, and more positive impact on professional life were reported in the last decade, likely secondary to less complication rates (all p < 0.001). Conclusion: This the longest follow up reports after living liver donation among German and Turkish populations. Although subject to recall bias, LOS was associated with negative impact on professional life and return to baseline functionality. Regret feelings were higher than literature. These long-term effects should be incorporated into donor discussions.